2016
DOI: 10.1007/s00701-016-2976-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of bone fragments in nonmissile compound depressed skull fractures

Abstract: Primary bone fragment replacement (after decontamination) is a safe option in the management of nonmissile CDSF within 72 h of trauma in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Eighteen articles were quantitatively analyzed following full-text analysis of the initial selected articles. These included 1 retrospective cohort study, 8 case series, and 9 case reports ( Table 1 ) [ 7 - 9 , 16 - 30 ] . Five studies were conducted in the United States, three in China, and one each in Brazil, Egypt, Germany, India, Indonesia, Japan, Nigeria, South Korea, Switzerland, and Turkey (10).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen articles were quantitatively analyzed following full-text analysis of the initial selected articles. These included 1 retrospective cohort study, 8 case series, and 9 case reports ( Table 1 ) [ 7 - 9 , 16 - 30 ] . Five studies were conducted in the United States, three in China, and one each in Brazil, Egypt, Germany, India, Indonesia, Japan, Nigeria, South Korea, Switzerland, and Turkey (10).…”
Section: Resultsmentioning
confidence: 99%
“…In the research performed by Wylen et al [11], no infection was detected in the study group consisting of 32 patients who underwent primary bone fragment replacement within the first 72 h after trauma. AbdelFatah [3] presented a study including 76 patients who underwent primary bone fragment replacement and found no infection in that series. In our study, infection was detected in only 2 of the 78 patients who were treated within the first 72 h after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, shortening the duration of contamination should be the main objective [5]. Although there are only a few studies in the literature showing that infection rates are high in operations performed with primary bone fragment replacement, in the last two decades, the rate of infection with primary bone fragment replacement has been found to be very low [3-5, 7, 9-11]. The infection rates are even lower, particularly in cases of intervention within the first 72 h after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of respondents highlighted similar surgical indications, for both open and closed fractures, as those previously described in literature reviews. 2 3 Infection rates in open fractures can be as high as 40% 12 however more contemporary series' have reported rates ranging from 0% 13 to 17%. 14 Primary bone replacement instead of delayed cranioplasty was the option of choice among most respondents.…”
Section: Surgical Indicationsmentioning
confidence: 99%